2016
DOI: 10.1111/jfpp.13104
|View full text |Cite
|
Sign up to set email alerts
|

Development of Shelf Stable Ready-to-Eat VegetablePulavUsing Radiation Technology

Abstract: The objective of this study was to develop a shelf stable ready‐to‐eat vegetable pulav, using radiation processing. The shelf stability of the product was assessed by microbial and sensory analysis during storage. A minimum dose of 7.5 kGy was found to be effective in controlling microbial growth in the product without compromising the sensorial quality up to 1 year of storage at the ambient temperature. Radiation processing up to 25 kGy dose did not alter proximate composition of the product. Marginal increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Mulmule et al (2017) reported that electron beam irradiation at 7.5 kGy or irradiation at 2.5 kGy followed by thermal treatment at 80°C for 20 min could eliminate the microorganisms in RTE Idli , a traditional Indian fermented food. In addition, gamma irradiation at 7.5 kGy was also found to be effective in controlling microbial growth in another Indian ethnic delicacy, RTE pulav , without compromising the sensorial quality at the ambient temperature (Marathe et al, 2017). Chen et al (2016) reported that gamma irradiation with the dose of 10 and 20 kGy could ensure the microbiological safety of the RTE stir fry chicken dices with hot chili without deterioration of sensory quality, although the germicidal efficacy of irradiation at dose <10 kGy was not investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mulmule et al (2017) reported that electron beam irradiation at 7.5 kGy or irradiation at 2.5 kGy followed by thermal treatment at 80°C for 20 min could eliminate the microorganisms in RTE Idli , a traditional Indian fermented food. In addition, gamma irradiation at 7.5 kGy was also found to be effective in controlling microbial growth in another Indian ethnic delicacy, RTE pulav , without compromising the sensorial quality at the ambient temperature (Marathe et al, 2017). Chen et al (2016) reported that gamma irradiation with the dose of 10 and 20 kGy could ensure the microbiological safety of the RTE stir fry chicken dices with hot chili without deterioration of sensory quality, although the germicidal efficacy of irradiation at dose <10 kGy was not investigated.…”
Section: Resultsmentioning
confidence: 99%
“…tive in controlling microbial growth in another Indian ethnic delicacy, RTE pulav, without compromising the sensorial quality at the ambient temperature(Marathe et al, 2017) Chen et al (2016). reported that gamma irradiation with the dose of 10 and 20 kGy could ensure the microbiological safety of the RTE stir fry chicken dices with hot chili without deterioration of sensory quality, although the germicidal efficacy of irradiation at dose <10 kGy was not investigated.…”
mentioning
confidence: 99%
“…Relatively lower initial microbial counts were perceived in RTE foods, which are previously heated, fried, or cooked before packing. Thus, successful sterilization and extension of the shelf life at ambient conditions of vegetable Pulav (stir‐fried and cooked vegetable, rice, and spices) for one year (Marathe et al, 2016), Bulgogi sauce for 3 months (Park et al, 2012), and stir fry chicken dices with hot chili for 12 months (Chen et al, 2016) has been reportedly approved at doses of 7.5, 10, and 10 kGy, respectively. However, the efficiency of ionizing irradiation on microorganisms could be enhanced by some factors.…”
Section: Resultsmentioning
confidence: 99%
“…For irradiated ready meals, a limiting factor for acceptability was the production of off odor, which could be assisted by including the strong flavor ingredients in the meals. The presence of spices in vegetable pulav (Marathe et al, 2016) and stir fry chicken dices with hot chili (Chen et al, 2016) might influence maintaining good acceptability scores even irradiation at 15 and 20 kGy. Therefore, panelists still accepted irradiated RTE shrimp chili paste, which contained many spices, after storage for 6 months under ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation